Analysis of a situational judgment test for teamwork as a preselection tool for an assessment center: A construct-based approach - Panja Goerke; Julia Maier (International Journal of Selection and Assessment, 2022)
Situational judgment tests (SJTs) constitute an efficient and well-established method for predicting professional success. However, more information is needed regarding their relationship to applicants' behavior as observed in an assessment center (AC) at the construct level. In the present study, an SJT for teamwork (SJT-TW) was assessed in terms of its suitability as a preselection tool for ACs in the context of a multistage selection. Data were collected from 276 applicants for ab initio pilot training during their selection process. Results from the regression analyses showed that the SJT-TW test performance is a significant predictor for the AC result and it contributed more than knowledge, cognitive performance tests, and personality scales thereto. The SJT-TW also caused significant increments for the prediction of single AC dimensions. Therefore, it was concluded that construct-based SJTs are useful for the assessment of behavioral constructs and can complement selection processes as a preselection tool.
Keywords: 650; assessment center; preselection; situational judgment test; teamwork